Association between everyday walking activity, objective and perceived risk of falling in older adults. (12th March 2021) - Jansen, Carl-Philipp; Klenk, Jochen; Nerz, Corinna; Todd, Chris; Labudek, Sarah; Kramer-Gmeiner, Franziska; Becker, Clemens; Schwenk, Michael
Abstract: Background: older persons can be grouped according to their objective risk of falling (ORF) and perceived risk of falling (PRF) into 'vigorous' (low ORF/PRF), 'anxious' (low ORF/high PRF), 'stoic' (high ORF/low PRF) and 'aware' (high ORF/PRF). Sensor-assessed daily walking activity of these four groups has not been investigated, yet. Objective: we examined everyday walking activity in those four groups and its association with ORF and PRF. Design: cross-sectional. Setting: community. Subjects: N = 294 participants aged 70 years and older. Methods: ORF was determined based on multiple independent risk factors; PRF was determined based on the Short Falls Efficacy Scale-International. Subjects were allocated to the four groups accordingly. Linear regression was used to quantify the associations of these groups with the mean number of accelerometer-assessed steps per day over 1 week as the dependent variable. 'Vigorous' was used as the reference group. Results: average number of steps per day in the four groups were 6, 339 ('vigorous'), 5, 781 ('anxious'), 4, 555 ('stoic') and 4, 528 ('aware'). Compared with the 'vigorous', 'stoic' (−1, 482; confidence interval (CI): −2, 473; −491) and 'aware' (−1, 481; CI: −2, 504; −458) participants took significantly less steps, but not the 'anxious' (−580 steps; CI: −1, 440; 280). Conclusion: we have integrated a digital mobility outcome into a fall risk categorisation based on ORF and PRF. Steps per day in this sample of community-dwelling older persons were in accordance with their ORF rather than their PRF. Whether this grouping approach can be used for the specification of participants' needs when taking part in programmes to prevent falls and simultaneously promote physical activity remains to be answered in intervention studies.